RETRACTED: Methods of power consumption in conditions of high-productive areas of coal mines - Reshetnyak Sergey; Golubov Evgeny (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001